Review on Energy Efficient LEACH Protocol in Wireless Sensor Network (International Journal of Engineering and Computer Science, 2016)
—  In Wireless Sensor network (WSN) the energy consumed by the sensor network determines the wireless sensor network lifetime and battery backup which effect lifetime of sensor node and nodes are alive more time. LEACH is a hierarchical routing protocol special for wireless network .LEACH due to randomness property CH selection and any sensor node become cluster head. More number of cluster in sensing reduce cluster size and energy consumption of nodes and cluster also data transfer between cluster head and base station. Stability is fail to maintain in system. The purpose is to increase the alive time of nodes for more data transfer among BS and CH without failure of any node. In improved LEACH protocol, after clusters are established, each cluster head decides whether to select a new cluster head, based on their energy consumption. The new cluster head will be the node having more residual energy. Thus, those clusters with less load can avoid the energy consumption resulted in selecting cluster head frequently. A homogeneous sensor network consists of identical nodes, while a heterogeneous sensor network consists of two or more types of nodes organized into hierarchical clusters